2010
DOI: 10.1088/0953-8984/22/15/155105
|View full text |Cite
|
Sign up to set email alerts
|

Ratchet dynamics of large polarons in asymmetric diatomic molecular chains

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Ratchet dynamics of solitons in nonlinear systems, described by nonlinear equations, such as sine-Gordon, was proven numerically (see, e.g., Zolotaryuk and Salerno [12], Gorbach et al [13]). Also it has been shown by Brizhik et al [14] that charged solitons can drift in molecular chains in the non-biased a.c. EMF. Appearance of such uni-directed motion is a critical phenomenon with respect to the intensity of the field and its frequency.…”
Section: Effect Of Emf On (Bi)solitonsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ratchet dynamics of solitons in nonlinear systems, described by nonlinear equations, such as sine-Gordon, was proven numerically (see, e.g., Zolotaryuk and Salerno [12], Gorbach et al [13]). Also it has been shown by Brizhik et al [14] that charged solitons can drift in molecular chains in the non-biased a.c. EMF. Appearance of such uni-directed motion is a critical phenomenon with respect to the intensity of the field and its frequency.…”
Section: Effect Of Emf On (Bi)solitonsmentioning
confidence: 95%
“…(8)- (9), γ is the friction coefficient, and q is the charge of a particle (q=e for a soliton, q=2e for a bisoliton, e is the elementary charge). In the simplest case the lattice potential is represented as a double-well periodic potential As it has been shown in Brizhik et al [14], such drift takes place only when the intensity of the field exceeds some critical value, which depends on the parameter values of the system, and in the fields whose frequency is not too high, namely, if it is less than the characteristic frequency of (bi)soliton (10) or (11), respectively. These conditions are necessary to allow (bi)soliton to overcome the potential barrier and the velocity (and frequency of oscillations) should be low enough so that the chain deformation could follow fast dynamics of electrons.…”
Section: Effect Of Emf On (Bi)solitonsmentioning
confidence: 99%
“…We adopt this Hamiltonian for our model, and following [12][13][14] we consider an additional external Hamiltonian,Ĥ ext , so that our Hamiltonian takes the form…”
Section: The Model and Dynamical Equationsmentioning
confidence: 99%
“…It should therefore be possible that polaronic a e-mail: b.m.a.g.piette@durham.ac.uk transport of electrons may take place in proteins, too. Recently, Brizhik et al reported on the properties of static and dynamical polarons in simple molecular chains, and adverted to the applicability of their results to electron transport in biomolecules such as proteins [12][13][14]. Their studies were based on the Davydov-Scott model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the chain itself, we have taken exactly the same parameters as in [57], i.e., C = 0.88 and G = 0.8, which correspond to the physical values of polypeptides and conducting polymers. For most of our simulations, we have used the value = 0.2.…”
Section: Parameter Valuesmentioning
confidence: 99%